Ag:TiN-Coated Polyurethane for Dry Biopotential Electrodes: From Polymer Plasma Interface Activation to the First EEG Measurements - Pedrosa, Paulo (2016)
Several plasma treatments using argon, oxygen, and nitrogen are studied in order to increase the interfacial adhesion of the polyurethane/Ag:TiN system to be used as biopotential electrodes. The optimized plasma treatments conditions (100 W, 15 min, regardless of the gas) promote a steep decrease of the water contact angle values. The observed chemical and topographic alterations translate into excellent polyurethane/Ag:TiN interfacial adhesion of the plasma treated samples. The in-service validation of the proposed Ag:TiN-coated PU multipin electrodes is performed by acquiring EEG signals in parallel with the standard wet Ag/AgCl electrodes. No considerable differences are found in terms of shape, amplitude, and spectral characteristics of the signals when comparing reference wet and dry electrodes.